Commissioning of a multi‐beamline femtoslicing facility at SOLEIL. (28th February 2018) - Labat, Marie; Brubach, Jean-Blaise; Ciavardini, Alessandra; Couprie, Marie-Emmanuelle; Elkaim, Erik; Fertey, Pierre; Ferte, Tom; Hollander, Philippe; Hubert, Nicolas; Jal, Emmanuelle; Laulhé, Claire; Luning, Jan; et al.
Abstract : The general layout of the femtoslicing facility at SOLEIL is presented. Abstract : The investigation of ultrafast dynamics, taking place on the few to sub‐picosecond time scale, is today a very active research area pursued in a variety of scientific domains. With the recent advent of X‐ray free‐electron lasers (XFELs), providing very intense X‐ray pulses of duration as short as a few femtoseconds, this research field has gained further momentum. As a consequence, the demand for access strongly exceeds the capacity of the very few XFEL facilities existing worldwide. This situation motivates the development of alternative sub‐picosecond pulsed X‐ray sources among which femtoslicing facilities at synchrotron radiation storage rings are standing out due to their tunability over an extended photon energy range and their high stability. Following the success of the femtoslicing installations at ALS, BESSY‐II, SLS and UVSOR, SOLEIL decided to implement a femtoslicing facility. Several challenges were faced, including operation at the highest electron beam energy ever, and achievement of slice separation exclusively with the natural dispersion function of the storage ring. SOLEIL's setup also enables, for the first time, delivering sub‐picosecond pulses simultaneously to several beamlines. This last feature enlarges the experimental capabilities of the facility, which covers the soft and hard X‐ray photon energy range. In this paper, the commissioning of this original femtoslicing facility is reported. Furthermore, it is shown that the slicing‐induced THz signal can be used to derive a quantitative estimate for the degree of energy exchange between the femtosecond infrared laser pulse and the circulating electron bunch.